2008
DOI: 10.1590/s1678-77572008000100007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the shrinkage stress of composite resins

Abstract: The aim of this study was to compare the shrinkage stress of composite resins by three methods. In the first method, composites were inserted between two stainless steel plates. One of the plates was connected to a 20 kgf load cell of a universal testing machine (EMIC-DL-500). In the second method, disk-shaped cavities were prepared in 2-mm-thick Teflon molds and filled with the different composites. Gaps between the composites and molds formed after polymerization were evaluated microscopically. In the third … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 20 publications
0
21
0
2
Order By: Relevance
“…The influence of the modulus of elasticity of composites on the stress generated during linear polymerization shrinkage has been studied previously by Pereira et al 1 In this investigation, the polymerization shrinkage of 4 commercial resin composites (Filtek Z250/3M ESPE, Filtek Supreme/3M ESPE, Admira/VOCO and Grandio/VOCO) were evaluated using 3 different methods: the magnitude of the stress generated during polymerization, linear polymerization shrinkage and wall-to-wall shrinkage in cylindrical cavities of bovine dentin; gaps in the second and third methods were examined by optical microscopy. The results showed that there were no significant differences in the magnitude of the stress generated; the Grandio composite had the highest values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of the modulus of elasticity of composites on the stress generated during linear polymerization shrinkage has been studied previously by Pereira et al 1 In this investigation, the polymerization shrinkage of 4 commercial resin composites (Filtek Z250/3M ESPE, Filtek Supreme/3M ESPE, Admira/VOCO and Grandio/VOCO) were evaluated using 3 different methods: the magnitude of the stress generated during polymerization, linear polymerization shrinkage and wall-to-wall shrinkage in cylindrical cavities of bovine dentin; gaps in the second and third methods were examined by optical microscopy. The results showed that there were no significant differences in the magnitude of the stress generated; the Grandio composite had the highest values.…”
Section: Discussionmentioning
confidence: 99%
“…The consequence of this "molecular contraction" in the material is a volumetric loss of approximately 1.5%. 1 Shrinkage promotes a deformation in the composite, which is clinically masked by the constraint of the bonded material, resulting in stress generation. 2 As the reaction proceeds, the stress increases and eventually becomes higher than the adhesives bond strength, causing gap formation.…”
Section: Introductionmentioning
confidence: 99%
“…Much research has been carried out to analyze the mechanical and esthetic properties of resin composites 21 in order to find an ideal material to replace lost dental structures. These studies have led to considerable scientific, industrial and technological development over the last few years, demonstrating their increasing use in anterior and posterior teeth 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been reported for evaluating polymerization shrinkage of resin composites, such as mercury dilatometer 16,21) , bonded disk method 22,23) , optical method 24,25) , use of the strain gauge 26) , liner shrinkage [27][28][29] etc. Monteiro et al compared the polymerization shrinkage of resin composites using three different methods; coordinate measuring machine (CMM), optical coherence tomography (OCT) and Archimedes' principle 30) .…”
Section: Discussionmentioning
confidence: 99%